Multiphase mixture model to predict temperature drop in highly choked conditions in CO2 enhanced oil recovery. (5th September 2016) - Teng, Lin; Zhang, Datong; Li, Yuxing; Wang, Wuchang; Wang, Lin; Hu, Qihui; Ye, Xiao; Bian, Jiang; Teng, Wenchao
Highlights: A new model is developed to predict the temperature drop for multiphase mixture. The characteristics of multiphase choked flow are studied experimentally. The model predictions are in good agreement with the experiment data. Effects of temperature drop for multiphase mixture through chokes are presented. Abstract: CO2 enhanced oil recovery (CO2 -EOR) technique is one potential option that can not only limit global warming, but also cut the high cost of Carbon dioxide Capture, Storage (CCS). It is well known that Joule-Thomson cooling (JTC) can occur when multiphase mixtures flow through wellhead chokes. To predict the temperature drop for multiphase mixtures with high CO2 content through choke valves, a new multiphase choked flow model was developed, which was based on the isenthalpic model, gas-liquid solubility equilibrium model and gas-liquid thermal equilibrium model. At the same time, a verification experiment was carried out to study on the flow characteristics in multiphase choked flow. The results also showed that the model predictions were in good agreement with the experiment data and HYSYS simulation results. It was found that choke valve pressure drop, gas components and gas-liquid ratio had impacts on the JTC. The positive contributions to JTC for CH4, N2 and H2 were decreasing gradually and high mole fraction of CO2 can enhance JTC. Based on this study, low GLR, low pressure drop and high upstream temperature can prevent freeze and block of the pipeline downstream.